Demographics and clinical burden of disease among RSV-hospitalized older adults in Italy: A retrospective cohort study - Anna Puggina; Melania Dovizio; Alexander Domnich; Alen Marijam; Chiara Veronesi; Caterina Rizzo; Marta Vicentini; Luca Degli Esposti; Giovanna Elisa Calabrò; Maria João Fonseca (Human Vaccines & Immunotherapeutics)
Respiratory syncytial virus (RSV) is a leading cause of acute respiratory infection and can lead to severe disease in older adults or those with comorbidities. This analysis aims to evaluate the demographic and clinical burden of RSV hospitalizations among older adults in Italy and inform potential preventative strategies. Adults aged ≥50 years with ≥1 hospitalization discharge diagnosis for RSV from 2010 to 2021 were included. Demographic characteristics before the first RSV hospitalization and clinical outcomes during this hospitalization and the 12 months following are described. Of the 243 patients, mean (SD) age was 73.7 (13.1) years, 40.7% were male, and the most common comorbidities were chronic obstructive pulmonary disease (37.9%), diabetes (21.8%), and heart failure (15.2%). Mean length of index hospitalization was 17.0 days, during which 9.1% of patients died. At index or during the 12-month follow-up, 5.8% had an intensive care unit admission, 61.3% were prescribed antibiotics, 8.2% had a stroke, and 3.3% had an acute myocardial infarction. During the 12-month follow-up, approximately, half of patients experienced worsening of preexisting comorbidities, with notable rates of re-hospitalization and mortality (44.4% and 29.6%). This study shows a high clinical burden of RSV among older adults in Italy, emphasizing a need for improved RSV surveillance, and may guide policymakers and healthcare providers in making informed recommendations for, and implementation of, RSV vaccination in Italy.